The relationship between emotional quotient and learning behavior of fourth year university students - Praditsang, Mali; Hanafi, Zahyah (MCSER Publishing, Rome-Italy, 2015)
This paper aimed to examine the relationship between emotional quotient and learning behavior of fourth year students at a university in the south of Thailand.Specifically the study examined 1) the level of emotional quotient and learning behavior, 2) the learning behavior of students with different personal factors and 3) the relationship between emotional quotient and learning behavior.The subjects were 520 fourth year students in the second semester of the 2012 academic year.The instrument used was a questionnaire consisting 3 parts: personal factors, emotional quotient and learning behavior. Percentage was used in analyzing the data on the level of emotional quotient and learning behavior and the findings revealed that the students had high levels of emotional quotient and learning behavior. Independent Group t-test and One-way ANOVA were used to compare the learning behavior of the subjects with different personal factors. It was found that students whose fathers had different levels of education and academic achievement had significantly different learning behavior.Pearson Correlations Coefficients test was used to test the relationship among variables, found that emotional quotient was positively correlated with the students’ learning behavior.